What is this link doing here? Beginning a fine-grained process of identifying reasons for academic hyperlink creation - Thelwall Mike (Information Research: An International Electronic Journal)
The purpose of this paper is to begin a [fine-grained] process of differentiating between creation motivations for links in academic Web sites and citations in journals on the basis that they are very different phenomena.